Regional Social Sustainability Index in Indonesia 2017 - Fahrulraz M. Faruk (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2020)
The realization of Social Sustainability is one of the important indicators of achieving sustainable development goals (SDGs) in 2030. The social aspect becomes an important indicator in measuring the achievement of sustainable development with a human approach as the subject. This study produces a composite index that will be used to compare social development between provinces in Indonesia. Besides, this study also analyzes the relationship between the Social Sustainability Index (SSI) formed, with the human development index (HDI) and GRDP per capita. This analysis is used to see the extent to which achievements in human and economic development affect social sustainability.